2015
DOI: 10.1007/s11356-015-5722-x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and genotoxic effects of chlorpyrifos in rats

Abstract: This study aims to investigate the effects of chlorpyrifos's sub-acute exposure on male rats. Two groups with six animals each were orally treated, respectively, with 3.1 mg/kg b w and 6.2 mg/kg b w of chlorpyrifos during 4 weeks. The genotoxic effect of chlopyrifos was investigated using the comet assay and the micronucleus test. Some hematological and liver's histopathological changes were also evaluated. Results revealed that chlorpyrifos induced histopathological alterations in liver parenchyma. The lympho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 44 publications
6
23
2
Order By: Relevance
“…and found dose-dependent comet formation at 24-h and 48-h exposure, which decreased with extended exposure times up to 96 h owing to DNA damage repair. Numerous studies have tested commercial formulations of chlorpyrifos on rats (Ezzi et al, 2016), mice (Chauhan et al, 2016), silkworms (Kalita et al, 2016) and fish (Ismail et al, 2014;Vera-Candioti et al, 2014), reporting the positive genotoxic effects. Even the occupational exposure to mixtures of insecticides including chlorpyrifos formulations has been associated with observed MN induction (Omari, 2011;Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…and found dose-dependent comet formation at 24-h and 48-h exposure, which decreased with extended exposure times up to 96 h owing to DNA damage repair. Numerous studies have tested commercial formulations of chlorpyrifos on rats (Ezzi et al, 2016), mice (Chauhan et al, 2016), silkworms (Kalita et al, 2016) and fish (Ismail et al, 2014;Vera-Candioti et al, 2014), reporting the positive genotoxic effects. Even the occupational exposure to mixtures of insecticides including chlorpyrifos formulations has been associated with observed MN induction (Omari, 2011;Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive data suggest that free radical formation and oxidative stress can be a major contributor to the toxicity of pesticides (108)(109)(110)(111)(112)(113). OPs are oxidants and impair enzymatic antioxidant defences, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione S-transferase (GST) (23,34,44,(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129). Malathion, methyl parathion, and parathion in HepG2 cell lines, as well as chlorpyrifos, methidathion, chlorfenvinphos, and dimethoate in rat liver and diazinon in fish most probably disrupt membrane lipids through oxidative stress (23,35,61,116,118,(130)(131)(132)(133)(134)(135).…”
Section: Possible Effects Of Ops On Hepatic Oxidative Stress Pathwaysmentioning
confidence: 99%
“…Goel et al (33) studied liver histoarchitecture in chlorpyrifostreated rats and observed hepatocyte vacuolisation and necrosis, sinusoidal dilatation, and increase in binucleated cells at higher doses and longer exposure to chlorpyrifos. Recent findings by Ezzi et al (34) suggest that chlorpyrifos had a dose-dependent effect on dilated sinusoids, central vein, and portal triad in rats.…”
mentioning
confidence: 95%
“…But only a few studies also addressed antigenotoxic effects (~6 %) like, e.g., Sassi et al (2016) who examined genotoxic as Results were drawn from the PubMed (total counts: 9091) and Web of Science™ Core Collection (total counts: 10,037) databases including the years from 1990 to 2016 using the search term "comet assay" well as antigenotoxic effects of Ceratonia siliqua extracts and total oligomer flavonoids in murine leukemia cells. In contrast, most of the publications investigated genotoxic effects of distinct substances like diazinon (Ezzi et al 2016b) or nano particles such as Ni nanoparticles (Magaye et al 2016). A limited number of studies (about 8 %) also analyzed oxidative-induced DNA damage using lesion-specific enzymes like FPG, Endo III or hOGG1 or DNA repair (about 7 %) in combination with the comet assay.…”
Section: Current Workmentioning
confidence: 99%